Lipoprotein Associated Phospholipase A2 Activity and It’s Additive Value inCardiovascular Risk Stratification - Andi W; Miryanti C; Saifur R; Dadang H; Widodo . (UNEJ e-Proceeding, 2014)
Background: Lipoprotein associated phospholipase A2  (Lp-PLA2) has been known as a useful  inflammatory marker of cardiovascular  risk. Framingham  score  has  also  been widely  used  in  long  term  cardiovascular  risk  stratification.  However,  it  remain  to  be clarified whether increased Lp-PLA2 activity and Framingham score significantly increase odd ratio (OR) in acute myocardial infarction (AMI) setting. We therefore investigated Lp- PLA2 activity  and  it’s  additive  value  for  Framingham  cardiovascular  risk  among myocardial infarction men.Blood samples were drawn from 60 men admitted to intensive care unit early after myocardial infarction and 40 healthy men with negative treadmill test as a control. Framingham score were calculated among all subjects. We measured Lp-PLA2 activity by ELISA. Lp-PLA2  activity was significantly higher in patients with myocardial infarction than those in control  (83.97±27.15  nmol/ml/minute  vs.  57.48±32.30  nmol/ml/minute; p=0.000). ROC analysis was performed to identify the most useful Lp-PLA2 cut-off level. Lp-PLA2 activity equal to or more than 74.21  nmol/ml/minute associated with myocardial infarction with accuracy 68%. The OR of AMI was increased by Lp-PLA2  activity added to Framingham score from 0.89(CI 95% 0.38- 2.11) to 4.48(CI 95% 1.90- 10.56) Conclusion:  Addition  of  Lp-PLA2   activity  to  Framingham  score  may  has  additive predictive value in cardiovascular risk stratification. Keywords: Lp-PLA2, myocardial infarction, cardiovascular risk stratification